An analytical and historical examination of six works for middle level wind band: Bells of freedom (grade 1) by David Gillingham, Rising star (grade 1) by Samuel R. Hazo, Achilles’ wrath (grade 2) by Sean O’Laughlin, Kenya contrasts (grade 2.5) by William Himes, On the wings of swallows (grade 3) by Michael Sweeney, and Old churches (grade 3) by Michael Colgrass - Riegel, Marcus L. (Kansas State University, 2009)
The following document is research and analysis from the comprehensive examination question based on the Graduate Conducting Recital of Marcus L. Riegel. The recital, performed by the Chapman Middle School Sixth, Seventh, and Eighth Grade Bands, was given in the District Gymnasium at the Spring Arts Concert on April 22, 2008 at 7:00 pm. The repertoire included but was not exclusive to Bells of Freedom by David Gillingham, Rising Star by Samuel R. Hazo, Achilles’ Wrath by Sean O’Loughlin, Kenya Contrasts by William Himes, On the Wings of Swallows by Michael Sweeney, and Old Churches by Michael Colgrass. This document contains theoretical and historical analysis- and outlines the procedures of planning and performing the graduate conducting recital.
Keywords: Middle level band literature; Music; Middle School Band; Band Literature; Education, Music (0522); Music (0413)